(untitled) (Advancements in Homeopathic Research, 2022)
Background: Writing manuscript is important in any discipline for the dissemination of new knowledge. Abstract and keywords are one of the most important parts of manuscript an editor or a reader looks for as it gives important points of whole paper as summary. Hence, knowledge on how to write a good abstract and keywords is a basic requirement for the authors to get their paper accepted, well indexed and good readability. In this paper, we review the literature as to how to write an abstract and keywords of scientific articles. Methods: Literature regarding writing abstract, as well as keywords of scientific articles was searched in the leading search engine Pubmed with the following search terms and their combinations: writing abstract, keywords, scientific article. Results: After different types of search, fifteen papers were selected based on their relevancy. Conclusion:Effective abstracts and keywords provide sufficient details of the whole paper without looking or reading the entire article saving a lot of time. This paper covers various aspects of writing abstract and keywordsof scientific article.